Characterisation of demoulding parameters in micro-injection moulding - Christian Griffiths (Microsystem Technologies, 2015)
Condition monitoring of micro injection moulding is an effective way of understanding the processing effects of variable parameter settings. This paper reports an experimental study that investigates the characteristics of the demoulding behaviour in micro injection moulding (µ-IM) with a focus on the process factors that affect parts’ quality. Using a Cyclic Olefin Copolyme (COC) microfluidics demonstrator, the demoulding performance was studied as a function of four process parameters (melt temperature, mould temperature, holding pressure and injection speed), employing the design of experiment approach. The results provide empirical evidences on the effect that processing parameters have on demoulding conditions in µ-IM, and identifies combinations of parameters that can be used to achieve the optimal processing conditions in regards to demoulding behaviour of micro parts. It was concluded that there was a direct correlation between the applied pressure during part filling, holding phases and the demoulding characteristic factors of the µ-IM cycle such as ejection force, integral and time.